Hakiki and Majāzi in Islamic Legal Interpretation: Implications for Gender Issues and Women's Rights - Tasliyah Erlina Ramli; Fatmawati; Zaenal Abidin (Lembaga Yasin AlSys, 2026)
The growing prominence of gender equality and women’s rights in modern society has intensified debates over the interpretation of Islamic law, particularly regarding whether Qur’anic and Prophetic texts should be understood through ḥaqīqah (literal meaning) or majāz (metaphorical meaning) in response to changing social realities. This study aims to analyze the concepts of ḥaqīqah and majāz within Islamic legal theory (uṣūl al-fiqh), examine their application to texts concerning gender and women’s rights, and assess their relevance to the contemporary reformulation of Islamic law. Employing a qualitative library research approach, the study draws on classical and contemporary works on uṣūl al-fiqh, Qur’anic exegesis, hadith studies, and Islamic legal scholarship. The findings demonstrate that ḥaqīqah and majāz constitute complementary interpretive instruments in understanding Islamic legal texts. In particular, metaphorical interpretation can reveal the broader objectives of Islamic law (maqāṣid al-sharīʿah) and support more context-sensitive responses to gender-related issues and women’s rights. Nevertheless, such interpretation must remain grounded in linguistic conventions, textual context, and established principles of Islamic jurisprudence to prevent arbitrary or subjective readings. The study concludes that a methodologically controlled application of ḥaqīqah and majāz can contribute to a more responsive, equitable, and contextually relevant framework of Islamic law. It further contributes to contemporary Islamic legal discourse by clarifying how classical linguistic principles may be employed to reconcile textual authority with evolving demands for gender justice.